Factors associated with the development of post-traumatic pain in patients at risk of post-traumatic osteoarthritis - Anastasia A. Bialik; Andrey E. Karateev; Maxim A. Makarov; Vadim A. Nesterenko; Valerii E. Bialik (Научно-практическая ревматология)
The aim of the study – to identify the factors associated with the development of chronic post-traumatic pain (CPTP) in patients with knee joint (KJ) injury.Materials and methods. The study group consisted of 136 patients (51.5% women, age 38.7±12.4 years) who suffered a KJ injury with damage to the anterior cruciate ligament and/or menisci. The inclusion criterion was the presence of pain in KJ ≥4 on a numerical rating scale (NRS 0–10) for at least 1 month after injury. Surgical intervention (plastic surgery of the anterior cruciate ligament, meniscus suture, meniscus resection, combined operations) was performed immediately after injury in 48.5% of patients. The incidence of CPTP was assessed (persistence of pain during movement ≥4 on NRS after 3 and 6 months of follow-up) and factors related to the development of CPTP. All patients were recommended to use orthoses of KJ, physical therapy and taking nonsteroidal anti-inflammatory drugs in the “on-demand” mode. Results. CPTP was detected after 3 months in 33.1%, and after 6 months in 32.4% of patients. Surgical treatment did not affect the development of CPTP: odds ratio (OR) – 1.241, 95% confidence interval (95% CI): 0.775–1.986 (p=0.474). The risk of CPTP after 6 months was statistically significantly higher in women, persons with a high body mass index (≥30 kg/m2), initially severe pain (≥7 on NRS), in the presence of initial signs of depression and anxiety (HADS (Hospital Anxiety and Depression Scale) ≥8) and highly probable central sensitization (CSI (Central Sensitization Inventory) ≥40): OR=2,152, 95% CI: 1,383–3,348 (p=0,002); OR=1,243, 95% CI: 1,054–1,465 (p=0,05); OR=3,567, 95% CI: 1,717–5,708 (p=0,001); OR=2,330, 95% CI: 1,070–5,726 (p=0.0044); OR=2,446, 95% CI: 1,220–4,905 (p=0,016); OR=2,584, 95% CI: 1,101–8,133 (p=0.043), respectively.